Systematic Review: Pengaruh Penggunaan Resep Elektronik terhadap Kejadian Kesalahan Pengobatan di Rumah Sakit - Putri, Maurilla Shafira; Dhamanti, Inge (LPPM Hang Tuah Pekanbaru, 2024)
Electronic prescribing systems are considered capable of facilitating the communication process related to pharmaceutical administration and services, as well as helping to translate prescriptions from doctors with pharmacists, patients, and other related medical personnel, to reduce the chances of medication errors occurring at the prescribing stage. This research article was conducted to determine the effect between the use of an electronic prescription system and the incidence of medication errors in the hospital. The research method used was a Systematic review study design conducted from May to June 2023. The Systematic review was based on data sources ScienceDirect, DOAJ, and Google Scholar with the keywords “electronic prescriptions” AND “medication errors” AND “patient safety”. From the extraction based on the inclusion and exclusion criteria, 9 selected articles were obtained. The results of the Systematic review showed that there was a positive effect of the use of electronic prescriptions on the incidence of medication errors in the hospital. So it can be concluded that the use of electronic prescriptions can reduce the incidence of medication errors in hospitals and improve the quality of health services.